Early morning fledging improves recruitment in Great Tits Parus major. (26th December 2014) - Radersma, Reinder; Komdeur, Jan; Tinbergen, Joost M.
Abstract : A potential key event linking the nestling phase to first‐year survival is fledging (nest leaving) because this process is characterized by a major change of environments and therefore a sudden shift in selective forces. Here we assessed whether different facets of fledging predicted subsequent survival (measured as local recruitment) in Great Tits Parus major . Nestlings had a higher recruitment probability when they fledged early in the morning and when they were heavy. The existence of selection for fledging early in the day has been suggested before, but here we provide the first empirical evidence in support of that prediction.